2006
DOI: 10.1111/j.1464-410x.2006.06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of primary hormone therapy for localized or locally advanced prostate cancer: results of a 10‐year follow‐up

Abstract: monotherapy or combined androgen blockade. They were followed until death, loss to follow-up, or until the end of the observation period (31 March 2004). We analysed all cases in each study as a single population, and compared Study 1 with Study 2. RESULTSThe mean patient ages were 67.2 years in Study 1 and 75.7 years in Study 2. During a median of 10.4 years of follow-up, 20 men in Study 1 and 17 in Study 2 died from prostate cancer, and 21 men in Study 1 and 50 in Study 2 died from other causes. In Study 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…In 2002, Labrie et al (2002) reported the efficacy of hormonal therapy for localized or locally advanced prostate cancer. In 2006, Akaza et al (2006) further confirmed the usefulness of PADT for localized or locally advanced prostate cancer by analyzing the 10-year survival rates for men with localized or locally advanced prostate cancer treated with PADT or prostatectomy. However, some patients who receive PADT, if followed long enough, will develop evidence of resistance and progression.…”
Section: Expression Of Pituitary Tumor Transforming Gene 1 Is An Indementioning
confidence: 94%
“…In 2002, Labrie et al (2002) reported the efficacy of hormonal therapy for localized or locally advanced prostate cancer. In 2006, Akaza et al (2006) further confirmed the usefulness of PADT for localized or locally advanced prostate cancer by analyzing the 10-year survival rates for men with localized or locally advanced prostate cancer treated with PADT or prostatectomy. However, some patients who receive PADT, if followed long enough, will develop evidence of resistance and progression.…”
Section: Expression Of Pituitary Tumor Transforming Gene 1 Is An Indementioning
confidence: 94%
“…Akaza et al 8 reported that overall survival rate of patients with localized or locally advanced prostate cancer treated with primary hormonal therapy was equivalent to life expectancy of age-matched subjects in the healthy population. Before Akaza's report, Egawa et al 9 had already reported that primary hormonal therapy was as effective as radical prostatectomy with regard to disease-specific survival rate in localized prostate cancer.…”
Section: Efficacy Of Primary Hormonal Therapy For Localized or Low-rimentioning
confidence: 99%
“…In terms of clinically localized prostate cancer, Labrie et al reported that approximately 80% of stage B prostate cancer could be controlled for long periods with PADT, 16 and recent analyses of practice patterns showed that many patients with localized cancer treated conservatively receive PADT rather than local treatment or active surveillance/watchful waiting. 17,18 Nevertheless, there have been no reports of instruments to predict outcomes for any population of previously untreated patients initiating PADT until the publication of the J-CAPRA derivation paper. 8 J-CAPRA was developed by analysis of a large database of a variety of patients undergoing PADT in Japan, and should be useful for clinical application to predict PADT in patients with not only advanced disease, but also localized cancer.…”
Section: Discussionmentioning
confidence: 99%